Trypsin inhibitor in winged bean tuber (Psophocarpus tetragonolobus) and its inactivation by heat - Monserrate, Joji U.
The level of activity of trypsin inhibitors in winged bean (Psophocarpus tetragonolobus) tuber sand and the effect of heat on these inhibitors were determined using the benzoyl-OL-arginine-p-nitroanilide in HCl (BAPA-HCl) assay for trypsin. The average level of trypsin inhibitor activity in 6 month old tubers was calculated to be 6.39 TIU/mg. tuber while in 8 to 9 month old tubers, the activity was 18.04 TIU.mg. tuber. The trypsin inhibitor in 8 to 9 month old tubers was completely inactivated after 19 minutes of streaming at atmospheric pressure and 38 minutes of baking at 325°F.